Pengaruh Budaya Senioritas terhadap Kepercayaan Diri Siswa - Nabila Safitri; Heru Mugiarso (Kuras Institute, 2022)
This study aims to determine the description of seniority culture, self-confidence description, and to analyze the influence of seniority culture on self-confidence in MTs students. in the district of Reban. The research was conducted using correlational descriptive quantitative research methods. The research subjects were 60 students from 151 students with a sampling technique that was simple random sampling. The instrument used in this study consisted of the Seniority Scale and the Confidence Scale. The validity of the test using the product moment formula and reliability using the alpha formula and to analyze the data using descriptive analysis and simple linear regression analysis.The results of the analysis show that the significance value for the influence of seniority culture on self-confidence is 0.000 <0.05 and the calculated F value is 7.692 > F table 1.671, so it can be concluded that there is an influence of seniority culture on self-confidence with the magnitude of the influence of seniority culture on self-confidence is by 50.5%